Designing a NAABSA Class Tanker Ship with Bottom Protection from Ground - Kulesh, Victor A.; Prasetio, Mathias Bimo; Hiep, Fam Chung (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
Indonesia is the world's largest archipelago country with a high potential for economic development and top producer and exporter of palm oil. As an archipelago country, the most efficient cargo transportation routes are through rivers and seas. Designing and building tankers, taking into account the specifics of the operation, are relevant. The paper considers the issues of designing a tanker for the transportation of crude palm oil with a defined operation area and route. The general concept of the vessel is proposed, taking into account the restrictions on the navigation area and draft for operation in the river. Particular attention is given to the issues of strengthening the hull in terms of overall longitudinal strength, as well as the bottom and the propeller-steering complex in terms of interaction with the ground. An external structural protection (ESP) from the ground was developed, and comparative calculations of the stress-strain state of the compartment and ESP structures were performed. The effectiveness of the solution for protecting the hull from direct contact with the ground is shown, and outlined ways for the possible development of tanker projects for the conditions.